2020
DOI: 10.1177/0145561320946908
|View full text |Cite
|
Sign up to set email alerts
|

Total Endoscopic Perichondrium Reinforced Cartilage Myringoplasty for Anterior Perforation

Abstract: Objectives: To investigate the outcomes of graft uptake and hearing results in the repair of anterior perforation via a total endoscopic transcanal approach using a single or double perichondrium reinforced cartilage underlay technique. Study Design: Retrospective study. Setting: Tertiary referral hospital. Materials and Methods: We analyzed 65 patients who underwent surgery for anterior perforation. All surgeries were done via an endoscopic transcanal approach using tragal cartilage as graft, underlay techniq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Previous studies showed that the graft success also depends on its location, besides the graft and the techniques used, the repair of an anterior or subtotal perforation is associated with a lower success rate than that of posterior or inferior perforations. 1 Although various surgical techniques were developed in recent years, these techniques required tympanomeatal flap elevation, or anterior canalplasty, and relatively advanced surgical skills to improve the anterior graft stabilization, which led to complicated surgical procedures, long operation time and slow healing. [4][5][6][7] In the cases of anterior protrusion of the EAC, it is difficult to remove the scar tissue of anterior margins, elevate the anterior tympanomeatal flap, and place the graft medial to anterior TM remnant even if endoscope is applied.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that the graft success also depends on its location, besides the graft and the techniques used, the repair of an anterior or subtotal perforation is associated with a lower success rate than that of posterior or inferior perforations. 1 Although various surgical techniques were developed in recent years, these techniques required tympanomeatal flap elevation, or anterior canalplasty, and relatively advanced surgical skills to improve the anterior graft stabilization, which led to complicated surgical procedures, long operation time and slow healing. [4][5][6][7] In the cases of anterior protrusion of the EAC, it is difficult to remove the scar tissue of anterior margins, elevate the anterior tympanomeatal flap, and place the graft medial to anterior TM remnant even if endoscope is applied.…”
Section: Discussionmentioning
confidence: 99%
“…They found that thinning or thickening of cartilage grafts did not prolong the operation or increased the technical difficulties; however, this did not lead to actual hearing gain or improved the success rate. [ 7 ] Therefore, in this study, we did not manipulate the thickness of the graft but directly removed most of the cartilage, leaving only the anterior strip-type structure. The results showed that our modification not only reduced the time for required graft shaping but also ensured postoperative hearing improvement and improved the graft success rate.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that TM perforations in the anterior quadrant are associated with lower surgical success rates than those in other quadrants because of insufficient visualization, poor vascularization, and poor stabilization. [ 7 ] The modifications of the underlay method include the mediolateral graft, window shade, loop overlay, and hammock techniques. Although improved, these operations necessitate postauricular incision, which extends the operating time and prolongs the postoperative recovery.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic otitis media is one of the common ear problems encountered by the otologist. 1 It can be divided as cholesteatomatous or noncholesteatomatous. 2 The pathogenesis of the cholesteatoma is still unknown.…”
Section: Introductionmentioning
confidence: 99%